2015
DOI: 10.11648/j.sjac.20150306.15
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, Spectroscopic and Chromatographic Characterization of Biofield Energy Treated Benzophenone

Abstract: Abstract:The aim of the present study was to evaluate the impact of biofield energy treatment on the thermal, spectroscopic, and chemical properties of benzophenone. The study was done using various analytical methods such as gas chromatography-mass spectrometry (GC-MS), high performance liquid chromatography (HPLC), differential scanning calorimetry (DSC), Fourier transform infrared (FT-IR) spectroscopy, and ultraviolet-visible (UV-Vis) spectroscopy. The benzophenone sample was divided into two parts, one par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Several aromatic solids displayed blended peak widths that are reported by OPUS as artificially narrow including the 3.3 cm −1 -wide feature in benzophenone at 1161 cm −1 (figures in the Supplemental Material). This corresponds to the ν 9b C–H in-plane deformation vibration of the phenyl rings 79,80 and was the narrowest band observed in the solids dataset. Note that the true peak width is in fact closer to 5–6 cm −1 as OPUS calculated the FWHM from a local baseline.…”
Section: Resultsmentioning
confidence: 99%
“…Several aromatic solids displayed blended peak widths that are reported by OPUS as artificially narrow including the 3.3 cm −1 -wide feature in benzophenone at 1161 cm −1 (figures in the Supplemental Material). This corresponds to the ν 9b C–H in-plane deformation vibration of the phenyl rings 79,80 and was the narrowest band observed in the solids dataset. Note that the true peak width is in fact closer to 5–6 cm −1 as OPUS calculated the FWHM from a local baseline.…”
Section: Resultsmentioning
confidence: 99%
“…Mr. Trivedi is one of the distinguished healing practitioners and has the astonishingly ability to transform the characteristic properties of several organic compounds [24][25][26], pharmaceuticals [27,28], nutraceuticals [29], metals and ceramic in materials science [30,31], culture medium [32,33] and improve the overall productivity of crops [34,35] as well as to modulate the efficacy of the various living cells [36][37][38]. Literature demonstrated that biofield energy treatment has the remarkable capability for alteration of the isotopic abundance ratio in the organic compounds [39][40][41][42]. Spectroscopic and thermal analysis of 3-CNB inferred that the physicochemical, structural and thermal properties of 3-CNB, such as crystallite size, vaporization temperature and thermal stability were significantly changed due to the biofield energy treatment.…”
Section: Figure 1 Structure Of 1-chloro-3-nitrobenzene (3-cnb)mentioning
confidence: 99%
“…Various scientific studies reported that Biofield Energy Healing have significant outcomes which showed more effective alternative, respective to other approaches [20]. Treatment have been reported scientifically to transform the characteristic properties of living organism and non-living substances in the field of microbiology [22][23][24], cancer cells [25], agricultural crops [26][27][28], pharmaceutical medium [29,30], material science [31,32], pharmaceutical compounds [33,34], nutraceutical [35][36][37], and organic compounds [38][39][40].…”
Section: Introductionmentioning
confidence: 99%